Long-term Treatment of Teicoplanin for Methicillin-resistant Staphylococcus aureus Sternal Osteomyelitis with Renal Impairment: A Case of High Teicoplanin Trough Levels Maintained by Therapeutic Drug Monitoring - Higa, Futoshi; Nakamura, Katsunori; Shiohira, Hideo; Kise, Yuya; Fujita, Jiro; Ueda, Shinichiro; Tateyama, Masao; Kuniyoshi, Yukio; Nakamatsu, Masashi; Hokama, Nobuo (YAKUGAKU ZASSHI, 2016)
Teicoplanin, a glycopeptide antibiotic for methicillin-resistant Staphylococcus aureus, is recommended for therapeutic drug monitoring during treatment. Maintaining a high trough range of teicoplanin is also recommended for severe infectious disease. However, the optimal dose and interval of treatment for severe renal impairment is unknown. We report a 79-year-old man who received long-term teicoplanin treatment for methicillin-resistant Staphylococcus aureus bacteremia due to postoperative sternal osteomyelitis with renal impairment. Plasma teicoplanin trough levels were maintained at a high range (20-30 μg/mL). Although the patient required long-term teicoplanin treatment, a further decline in renal function was not observed, and blood culture remained negative after the start of treatment. Teicoplanin treatment that is maintained at a high trough level by therapeutic drug monitoring might be beneficial for severe methicillin-resistant Staphylococcus aureus infection accompanied by renal impairment.